Peran Ustadz Dalam Meningkatkan Pemahaman Agama Islam Terhadap Mu’allaf Di Markaz Dakwah - Karliana Indrawari; Azwar Hadi; Madi Apriadi (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
This study aims to determine the history of the founder of the Da'wah Markaz; to know the progress from the year of establishment until now; to find out what methods used ustadz in learning. The research method used is the field study research method. Data collection techniques in this study using observation, interviews and documentation. Data analysis techniques using Miles and Huberman, namely data reduction, data presentation, and data conclusions. The results of the study are the city of Palembang is the place where the headquarters of Da'wah was established, because there is no conflict between religions or races. Education and development of learning delivered by the clerics in the propaganda markers as follows: Aqeedah and Morals, Fiqh of worship, Prophetic God, and Tilawatil or recitation of the Qur'an. As for the various teaching methods conducted by the cleric to convert Muslims to improve understanding of the Islamic religion are: lecture method, question and answer method, and method of giving assignments.